PSYCHOLOGICAL AND PEDAGOGICAL SUPPORT OF PERSONALITY FORMATION IN THE MODERN CONCEPT OF PROFESSIONAL EDUCATION - Kuzhanova, Natalya; Pak, Tatyana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In the educational space for vocational education, several dominants are currently being formed. The main ones are: use of all available educational content through online courses and distance education, an individual trajectory and a unique set general cultural, general professional competencies for formation of a model of a future specialist in the context of strategic thinking, development of tactics and a system of indicators for achieving, the strategic goal of vocational education, consideration of the greatest possible number of risks associated with the implementation of life activities in the broadest context for the planned period of time for obtaining a vocational education (risks of being, risk of updating the acquired knowledge and skills for the formation of professional competencies, risks of personal growth or degradation, etc. The article discussed the pedagogical system of psychological and pedagogical support for the personality of the student to implement his individual learning path. With its implementation, as a result, for formation of a future specialist is expected with a unique setoff competencies that will allow a future specialist to realize himself in the chosen field of activity and the necessary professional level. The article discusses the structure of the named pedagogical system, its main elements and their characteristics for the formation of an individual risk-balanced style of professional activity. The concept of the style of risk-balanced professional activity is copyright.